Perancangan Ulang Lifting Table sebagai Alat Bantu Welder di Industri Pressure Vessel - Maulana Putra Setiawan; I Putu Sindhu Asmara; Tri Andi Setiawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
Lifting table is a tool to help welders who do welding in high places. Pressure vessel industry does not have drawings data of lifting table so that there are no guidelines for the manufacturing flow, according to questionnaires and interviews with welders, this lifting table does not have mobility and its operation still involves 2 (two) workers so it is less efficient. Drawings data of existing products and redesign product lifting table were made using the Ulrich Method by selecting 1 (one) best concept from several concepts that had been previously selected, then do strength analysis, ergonomics analysis and production cost analysis. Based on the results of the analysis, existing product lifting table has a 42,17 kN buckling value, work platform stress analysis is 16,71 MPa and a ladder stress analysis is 8,62 MPa. The redesign product of lifting table has a minimum buckling value of 67,56 kN, a stress value of 9,22 N/mm2 and a deflection value of 2.64 mm, a redesign lifting table has 4 score in ergonomics analysis and Rp. 9,604,000 to manufacture it.